ASSESSMENT OF SEA CUCUMBER FISHERY IN THE MULLAITIVU COASTAL WATERS IN NORTH-EAST, SRI LANKA - Dalpathadu, Kasun Randika; Haputhantri, Sujeewa Sisira Kumara; Kitakado, Toshihide (Indonesian Fisheries Research Journal, 2023)
The sea cucumber is one of the key export-oriented fishery resources in Sri Lanka. There are some evidences for overexploitation of most of the sea cucumber species in the shallow coastal waters. The present study was undertaken with the aim of understanding the status of the sea cucumber fishery in the Mullaitivu district in the North-east Coast of Sri Lanka and to carry out a stock assessment on the key sea cucumber species presently harvested from this area. To achieve this objective, the sea cucumber fishing season in 2019 (March – August) was based and the personal logbook records of the 12 sea cucumber collectors were used as the primary data source. Two species, Bohadschia vitiensis and Holothuria spinifera were dominant contributing 83 % and 16 % to the total catch respectively. The average Catch Per unit Effort (CPUE) during the fishing season in 2019 was 178±224 individuals boat-1day-1 and a sharp decline in the average monthly CPUE of both species was observed towards the end of the fishing season. The stock of the B. vitiensis in the Mullaitivu fishing ground was assessed using the depletion method. The initial stock size of B. vitiensis at the onset of the fishing season was estimated at 432,549 individuals and more than 90 % of the initial stock had been fished by the end of the fishing season. The study revealed that the stock of B. vitiensis along with other recorded species in the Mullaitivu waters is at a high risk at present.